The Construction of Citizenship Imagination and İdeological Apparatuses in the Early Republican Period - Kandeğer, Barış (Journal of Applied And Theoretical Social Sciences, 2025)
Introduction: This article reveals the multifaceted role of ideological apparatuses in constructing citizenship as envisioned by the founding authority of the Early Republican regime. Method: A historical analysis was employed in relation to the scope of the subjectand primary and secondary sources concerning imagined citizenship during the Early Republican Period were selected and analyzed. Results or Findings: During this period, ideological apparatuses played a multifaceted role in constructing imagined citizenship, strengthening the Republican regime, building a modern nation-state on solid foundationsand establishing the intellectual and practical infrastructure for a modern, civilized life compatible with the Republic. Discussion or Conclusions: During this period, imagined citizenship was conceived and attempted to be realized within an identity capable of modernization and development. This identity was aligned with positivist and secular thought and belonged to the regime within the field of action created by ideological Apparatuses. During this period, political authority made ideological apparatuses functional in a broad, multifaceted way within a framework of political subjects in order to construct citizenship.